2021
DOI: 10.2174/1389450122666210303100048
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Early Detection of Colorectal Cancer: A Focus on Non-invasive Biomarkers

Abstract: Background: Colorectal cancer (CRC) is the third most commonly diagnosed cancer Worldwide. Currently, colonoscopy remains the gold standard diagnostic test for CRC detection. Nonetheless, this technique is invasive and expensive. Remarkable ongoing strategies are focusing on development affordable methods to diagnosis at earlier stages and surveille CRC. The introduction of suitable noninvasive, sensitive and specified diagnostic tests for early CRC detection by employing biomarker analysis seems to be a fund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…For instance, stool or other bodily fluids, including urine and ascites, have been attracting attention as novel non‐invasive tools for CRC detection and monitoring. 128 , 129 , 130 Colorectal mucus is an important component of the protective intestinal barrier, and the loosened colorectal mucus may lead to severe disorders, including colitis and tumour initiation. Thus, this new method of colorectal mucus sampling can also provide highly informative material and present a simple and efficient method for IBD detection.…”
Section: Clinical Application Of Non‐coding Rnas In Cac Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, stool or other bodily fluids, including urine and ascites, have been attracting attention as novel non‐invasive tools for CRC detection and monitoring. 128 , 129 , 130 Colorectal mucus is an important component of the protective intestinal barrier, and the loosened colorectal mucus may lead to severe disorders, including colitis and tumour initiation. Thus, this new method of colorectal mucus sampling can also provide highly informative material and present a simple and efficient method for IBD detection.…”
Section: Clinical Application Of Non‐coding Rnas In Cac Patientsmentioning
confidence: 99%
“…First, in addition to the information from blood or colon tissues, we still need to focus on some other sources of clinical samples. For instance, stool or other bodily fluids, including urine and ascites, have been attracting attention as novel non‐invasive tools for CRC detection and monitoring 128–130 . Colorectal mucus is an important component of the protective intestinal barrier, and the loosened colorectal mucus may lead to severe disorders, including colitis and tumour initiation.…”
Section: Clinical Application Of Non‐coding Rnas In Cac Patientsmentioning
confidence: 99%
“…Several susceptibility studies on the association of a genetic variant and CRC have been reported [ 5 ]. The solid tumors of CRC have served as genetic and biological paradigms and instigated to conduct studies on early detection [ 6 ], prevention [ 7 ], risk stratification [ 8 ], and treatments [ 9 ]. However, a greater understanding and identification of genetic biomarkers involving molecular and genetic pathways with improved sensitivity and specificity could improve screening for and expedite the diagnosis of CRC, yielding better outcomes.…”
Section: Introductionmentioning
confidence: 99%